Smoking and Incidence of Colorectal Cancer Subclassified by Tumor-Associated Macrophage Infiltrates. (15th July 2021) - Ugai, Tomotaka; Väyrynen, Juha P; Haruki, Koichiro; Akimoto, Naohiko; Lau, Mai Chan; Zhong, Rong; Kishikawa, Junko; Väyrynen, Sara A; Zhao, Melissa; Fujiyoshi, Kenji; Dias Costa, Andressa; Borowsky, Jennifer; et al.
Abstract: Background: Biological evidence indicates that smoking can influence macrophage functions and polarization, thereby promoting tumor evolution. We hypothesized that the association of smoking with colorectal cancer incidence might differ by macrophage infiltrates. Methods: Using the Nurses' Health Study and the Health Professionals Follow-up Study, we examined the association of smoking with incidence of colorectal cancer subclassified by macrophage counts. Multiplexed immunofluorescence (for CD68, CD86, IRF5, MAF, and MRC1 [CD206]) combined with digital image analysis and machine learning was used to identify overall, M1-polarized, and M2-polarized macrophages in tumor. We used inverse-probability–weighted multivariable Cox proportional hazards regression models to control for potential confounders and selection bias because of tissue data availability. All statistical tests were 2-sided. Results: During follow-up of 131 144 participants (3 648 370 person-years), we documented 3092 incident colorectal cancer cases, including 871 cases with available macrophage data. The association of pack-years smoked with colorectal cancer incidence differed by stromal macrophage densities ( P heterogeneity = .003). Compared with never smoking, multivariable-adjusted hazard ratios (95% confidence interval) for tumors with low macrophage densities were 1.32 (0.97 to 1.79) for 1-19 pack-years, 1.31 (0.92 to 1.85) for 20-39 pack-years, and 1.74 (1.26 to 2.41) for 40 or more pack-years ( P trend = .004). In contrast, pack-years smoked was not statistically significantly associated with the incidence of tumors having intermediate or high macrophage densities ( P trend > .009, with an α level of .005). No statistically significant differential association was found for colorectal cancer subclassified by M1-like or M2-like macrophages. Conclusions: The association of smoking with colorectal cancer incidence is stronger for tumors with lower stromal macrophage counts. Our findings suggest an interplay of smoking and macrophages in colorectal carcinogenesis.